Pendekatan Guru IPS dalam Penguatan Sikap Toleransi: Studi Kasus pada Madrasah Tsanawiyah (MTs) di Kota Bengkulu - Irwan Satria; Budrianto Budrianto (Indonesian Journal of Social Science Education (IJSSE), 2024)
The problem of tolerance is one of serious problem in Indonesia. A number behavior and intolerance cases are proof that inhancancing tolerance attitude is very needed, including through Islamic education institution, especially through social studies learning in Madrasah Tsanawiyah. The amis of this research are: 1) describe the understanding and perspectives of social studies teachers of strengthening tolerance attitude; and 2) describe social studies teachers approach in strengthening tolerance attitude in Madrasah Tsanawiyah. This study was a qualitative (case study tife) research. The object of the study was social studies teacher in Madrasah Tsanawiyah in Bengkulu City. Data were elicited using interviews, questionnaires, document analysis and observation. Data analysis was carried out using an interactive model of Milles & Huberman. Based on the research, the results obtained are:1) Social studies teachers at MTs Bengkulu city views that toletance needs to be instilled, especially because it in line with Islamic religious teanhing, relevance to the vision of social studies learning and because of the encouraging socio-cultural reality of the Indonesian people; and 2) there are three main approaches that aer applied by teachers in strengthening tolerance, namely religious moderation which aims to introduce a moderate way of religion, especially through the teaching of Islam, multicultural education apptroach that seeks to instill the principles of unity in diversity to Indonesia is a multicultural, and character education approach that seeks to instill the value of tolerance to students through the process of value